CSR communications on social media : using social media to promote CSR communications - Saga Ýr Kjartansdóttir 1991- (2018)
Companies that participated in this research are Icelandic small and medium sized (SMEs) and large firms that have or are thinking about developing their CSR activities. Little emphasis has been on connecting social media and CSR activities as an initiative to communicate CSR, especially for its relevance to newness and change in technology and business development in Icelandic firms. The purpose of this study is to examine how Icelandic companies use social media to promote corporate social responsibility (CSR) activities, and how it can help companies to meet their strategic goals to increase business growth. Furthermore, to understand whether and how companies use social media to communicate their CSR activities. Little is known about whether and how Icelandic companies use social media to communicate their CSR for marketing purposes and practice. This research will contribute to this gap. Qualitative multiple case study approach using semi-structured in-depth interviews was conducted on the company’s focus on marketing directors or communication´s directors. The results from the interviews indicate newness in approach to marketing - firms are showing signs toward incorporating social media strategically to communicate the firms CSR activities. Keywords: CSR, social media, communication, CSR reporting, marketing, Iceland.